Seismic activity in Costa Rica during 2012 - Linkimer, Lepolt (2011)
During 2012, the National Seismological Network (RSN: UCR-ICE) recorded 3455 local earthquakes and reported 260 felt events. This high level of seismicity was mainly the result of the aftershocks and triggered seismicity of the Samara earthquake on 5 of September (Mw 7,6). There were also 12 significant earthquakes with magnitude ≥ 5,0. The majority (90%) of earthquakes were shallow (< 30 km) and 56% had low magnitude (Mw 3,0- 3,9). The subduction of the Cocos Plate beneath the Caribbean Plate and the Panama microplate generated 53% of felt earthquakes. Local faults originated 45% of felt seismicity, mainly in the Central Valley, the Calero Island, and the Coto Brus regions. The highest intensity observed during 2012 was VII (Modified Mercalli, MM) in the Nicoya Peninsula and in the Zarcero-Naranjo region due to the Samara earthquake. Moreover, eight other earthquakes produced inten- sities of V (MM).